An Ontology for Context-aware Middleware for Dependable Medical Systems - Cerqueira, Jorsiele (Companion Proceedings of the Latin-American Symposium on Dependable and Secure Computing (LADC); 2022: Companion Proceedings of the 11th Latin-American Symposium on Dependable Computing, 2022)
In healthcare systems, there is an ecosystem of heterogeneous biosensors. A middleware is required for transmitting and establishing dependable communication with multiple integrations and information exchange through messages. However, in environments in which a distributed and dynamic network exists, a purely traditional middleware would not minimize the effect failures at data transmission and network congestion can cause. To preserve data integrity and provide relevant services as the environment changes, the use of context-aware middleware is recommended. This article describes an ontology for context-aware middleware to handle challenges faced by medical system networks and environment changes.